Preparation and Characterization of PEG-PLA Genistein Micelles Using a Modified Emulsion-Evaporation Method - Wu, Jizhou; Li, Guojian; Yu, Yanhong; Qin, Wen; Cheng, Qiuchen; Zhuo, Lang (Journal of nanomaterials, 2020)
The objective of this study is to improve the bioavailability of genistein by encapsulation with polyethylene glycol-polylactic acid (PEG-PLA) copolymers. Genistein micelles (GMs) prepared using a modified emulsion-evaporation method were more stable than those made with the original method. The effect of polyvinyl alcohol, Tween 80, sonication time, PEG-PLA/genistein ratio, and organic phase (acetone)/H2O ratio on the size, polydispersity index, encapsulation efficiency, and drug loading efficiency of GMs was investigated. GMs were obtained and characterized under optimal experimental conditions. For long-term storage, GMs were lyophilized by freeze drying with trehalose to produce genistein lyophilized powder (GLP). The analysis of GLP by Fourier-transform infrared spectroscopy and differential scanning calorimetry showed that genistein was successfully incorporated into the micellar structure. In vitro release experiments revealed that the incorporation of genistein into PEG-PLA copolymers significantly improved its solubility and bioavailability. GLP was more potent in inhibiting the proliferation of HSC-T6 cells than genistein. Treatment with GLP at 10–20 μg/mL for 48 h significantly inhibited the protein expression of α-smooth muscle actin and collagen I in HSC-T6 cells compared with the control. These data demonstrated that the improved solubility and bioavailability of genistein in the form of GLP enhanced its antifibrotic effect in vitro.